Community Perception and Spatial Diaper Waste in Liliba Village, Kupang City - Tarigan, Lidia Br; Dukabain, Olga Mariana; Telan, Albina Bare; Sadukh, Johanis J.P. (Syntax Corporation Indonesia, 2025)
The improper management of diaper waste in Liliba Village, Indonesia, poses a serious environmental and public health concern. Currently, diaper waste is often discarded indiscriminately without prior processing, resulting in unpleasant odors and public complaints. This study aims to analyze community perceptions regarding diaper waste and to map its spatial distribution within Liliba Village. Employing an observational research design, the study investigated two main variables: public perception of diaper waste and the spatial distribution of diaper waste. A total of 111 respondents, all of whom were parents of toddlers, were selected as the study sample. Data were collected using structured questionnaires and Geographic Information System (GIS) applications. Analysis was conducted using univariate and bivariate statistical techniques. The results indicate that both gender and occupation significantly influence community perceptions of diaper waste and their views on proper waste management. Spatial analysis revealed that diaper waste is primarily found in temporary disposal sites (TPS) and in various unregulated locations, especially within the buffer zones surrounding residential areas of the respondents. These findings highlight the urgent need for targeted waste management education and infrastructure development to improve sanitation practices in Liliba Village. The integration of spatial data through GIS provides valuable insights for local authorities to implement geographically focused waste intervention strategies.